Proses Pengembangan Ekonomi Kreatif Sebagai Suatu Pekerjaan Institutional - Jurry Hatammimi; Marianne Afanassieva (Jurnal Manajemen Indonesia, 2022)
Although experiencing an underdeveloped institutional environment, there is a significant contribution of Indonesia’s creative economy to the national economy. Therefore, it is important to investigate the process of creative economy development in Indonesia, as an emerging market. This research investigates an underdeveloped institutional environment confronted by the creative economy actors and how they face this environment in Bandung city. The method used by this research is multiple case studies that mainly collect data by conducting in-depth interviews from the quadruple helix entities. It is found that the bottom-up approach was organically implemented in the creative economy development process in Bandung. This conduct was based on the cultural-cognitive institutional pillar and showed a community as the institutional entrepreneur that spanned an institutional void. This research can be considered as a pioneer in institutional entrepreneurship studies which focus on the creative economy in emerging markets. Further study can utilize the Penta helix approach to expand the result of this research. Keywords— creative economy; emerging market; institutional entrepreneur; institutional work.